A multi‐objective approach for improving real‐time audio peak reduction and speech clarity in a dental drill noise reduction device. Issue 7 (2nd May 2021) - Jiang, Pingfei; Atherton, Mark A.
Abstract: Audio signals typically comprise several characteristics to be improved by signal processing and in practice, each of these characteristics has a unique relationship to the controllable system parameters. Quantifying these relationships in a multi‐objective (MO) approach will enable an improved system setup. This paper determines two novel objective functions of a complex audio signal for the real‐time simultaneous improvement of audio peak reduction and speech clarity in a dental drill noise reduction (DDNR) device. The influence of the DDNR system parameters on the outcome of peak reduction and speech clarity is determined by combining response surface methodology and a desirability function to enable MO optimisation. The results show an average improvement of nearly 30% over the original DDNR device performance. The approach described provides an effective means for addressing MO optimisation of other real‐time audio signal processing applications where the signal has similar peak reduction and speech clarity objectives to be processed, particularly where the physical outcome is not easy to evaluate in a virtual environment.